(untitled) (The Strategic Review for Southern Africa, 2022)
Small scale mining largely remains an informal and unexplored economic sector. Mining is generally dominated by big players in the form of multinational corporations (MNCs) who are characterised by large scale for profit production at the expense of smaller players. In particular, the participation of youth and women in extractive industries is usually restricted to either illegal or small-scale mining. Whilst artisanal and smallscale mining (ASM) is promising and has a potential in terms of employment creation and enterprise development, this sector remains at the periphery of options and is deemed the sector of last resort for most youth and women. The sector is marked by lack of government regulation and neglect with regards to issues of safety, health and environmental protection. Observations from across the African continent and the rest of the developing world indicate that ASM is a formidable source of employment and economic development for poor communities. It could therefore be argued that for youth and women on the continent ASM proffers opportunities and thus needs to be formalised and promoted as a viable option for economic participation especially within poor communities. Using secondary data sources, this paper foregrounds the cooperatives approach, as championed across sectors in South Africa, as a tried and tested model that could be replicated across the Southern African Development Community (SADC) region to complement existing policy instruments such as the SADC mining protocol and the African Union (AU) Mining Vision. This paper contends that cooperatives offer a low entrance barrier type of formalisation of ASM initiatives for youth and women whereby legal entities within the extractive industries could be established.